Examination of Teachers' Views on Metaverse-Based Education - Semerci, Nuriye; Sağ, Mert; Özçelik, Ceyda; Semerci, Nuriye (STAR Scholars Network, 2024)
The aim of this study is to determine teachers' views on metaverse-based education. The research is qualitative and was conducted with a phenomenological design. The maximum diversity sampling technique, one of the purposeful sampling methods of the study group, was used. In this direction, data were collected from as many different teachers as possible, including their age, field of study, school type, and gender. The research was carried out with 32 teachers. The data were collected through face-to-face interviews using a semistructured interview consisting of four questions about personal information and 11 questions about the metaverse. The data were analyzed by a descriptive analysis method using MAXQDA software. Teachers stated that the integration of metaverse technology into education and training processes will increase the quality, efficiency and permanence of this process. © 2024 Elsevier B.V., All rights reserved.
Keywords: Metaverse; Metaverse-Based Education; Technology; Virtual Universe